EULAR standardised training model for ultrasound-guided, minimally invasive synovial tissue biopsy procedures in large and small joints - Annamaria Iagnocco; Andrew Filer; Gabriel Herrero-Beaumont; Peter Balint; Ingrid Moller; Esperanza Naredo; Lene Terslev; Alessandra Bruns; Aurélie Najm; Ana Rodriguez; Raquel Largo; Stefano Alivernini; et al. (RMD Open)
Objectives To develop an EULAR training model for education in synovial tissue biopsy (STB) under ultrasound guidance (UG) following a stepwise approach: (1) development of educational material on UGSTB in large and small joints; (2) assessment of the validity, reliability and feasibility of the UGSTB educational procedure on cadaveric specimens; (3) validation of this procedure in live patients.Methods Using a nominal group (NG) and a DELPHI consensus methodology, educational audio-visual (AV) material and minimal requirements for education in UGSTB were developed by an expert panel. Then the experts performed an UGSTB on cadaveric joints using the developed approach. The samples retrieved from the cadaveric joints were confirmed histologically and the procedure was then tested by a group of ultrasonographers with different expertise for feasibility and face validity. The AV material and the practical procedures’ phases were subsequently ranked by the experts to finalise the training model for performing UGSTB in patients. The ST retrieved in patients was assessed for tissue quality.Results Based on NG and DELPHI processes, educational material and a stepwise standardised cadaver-based training model were developed. The knee was the cadaveric joint with the highest yield of histologically good quality of ST. 90% of the UGSTB from patients showed synovial membrane and 77% intact lining layer.Conclusions This EULAR endeavour provided a consensus-based comprehensive educational material and a practical cadaver-based model for training in UGSTB, which has shown feasibility and validity in tissue acquisition in specimens and patients.